To find rules (or formulas) that may be used solve any system of equations, we need to solve the general system of the form
a_{ 1} x + b_{ 1} y = c_{ 1} (1)
a_{ 2} x + b_{ 2} y = c_{ 2} (2)
We multiply equation (1) by b_{ 2} and equation (2) by b_{ 1} and add the right and left hand terms.
b_{ 2} a_{ 1} x + b_{ 2} b_{ 1} y = b_{ 2} c_{ 1} (1)
 b_{ 1} a_{ 2} x  b_{ 1} b_{ 2} y =  b_{ 1} c_{ 2} (2)
____________________________
b_{ 2} a_{ 1} x  b_{ 1} a_{ 2} x = b_{ 2} c_{ 1}  b_{ 1} c_{ 2}
Assuming that a_{ 1} b_{ 2}  a_{ 2} b_{ 1} is not equal to zero, solve the above equation for x to obtain.
x = ( c_{ 1} b_{ 2}  c_{ 2} b_{ 1} ) / ( a_{ 1} b_{ 2}  a_{ 2} b_{ 1} )
We can use similar steps to eliminate x and solve for y to obtain.
y = ( a_{ 1} c_{ 2}  a_{ 2} c_{ 1} ) / ( a_{ 1} b_{ 2}  a_{ 2} b_{ 1} )
Using the determinant of a Matrix
notation, the solution to the given 2 by 2 system of linear equations is given by
x = D_{ x} / D and y = D_{ y} / D
where D, D_{ x} and D_{ y} are the determinants defined by
For a 3 by 3 system of linear equations of the form
a_{ 1} x + b_{ 1} y + c_{ 1} z = d_{ 1} (1)
a_{ 2} x + b_{ 2} y + c_{ 2} z = d_{ 2} (2)
a_{ 3} x + b_{ 3} y + c_{ 3} z = d_{ 3} (3)
Cramer's rule gives the solution as follows
x = D_{ x} / D , y = D_{ y} / D and z = D_{ z} / D
where D, D_{ x}, D_{ y} and D_{ z} are determinants defined by
Example: Use Cramer's rule for a 3 by 3 system of linear equations to solve the following system
2 x  y + 3 z =  3
 x  y + 3 z =  6
x  2y  z =  2
Solution:
Determinants D, D_{ x}, D_{ y} and D_{ z} are given by (see how to Calculate Determinant of a Matrix.)
D = 21
D_{ x} = 21
D_{ y} = 42
D_{ z} = 21
We now use cramer's rule to find the solution of the system of equations
x = D_{ x} / D= 1
y = D_{ y} / D= 2
z = D_{ z} / D= 1
As an exercise check that (1,2,1) is a solution to the given system of equations.
References and links related to systems of equations and determinant.
